HUBUNGAN TINGKAT PENGETAHUAN INFEKSI NOSOKOMIAL DENGAN SIKAP PENGGUNAAN APD MAHASISWA ANESTESIOLOGI PADA SAAT PRAKTIK KLINIK - diffa, denintia (STIKES Borneo Cendekia Medika, 2024)
Background: Infection is the main cause of high morbidity and mortality in the world, with a prevalence of 6.1%-16.0% in developing countries such as Indonesia. Prevention of nosocomial infections requires the implementation of Standard Precautions and the use of Personal Protective Equipment (PPE), which requires good knowledge and attitude from health workers, including students. Objective: The objective of this study is to determine the relationship between the level of knowledge of nosocomial infections and the attitude of anaesthesiology students regarding the use of PPE during clinical practice. Method: This study was a descriptive correlational study with a cross-sectional approach on 105 anaesthesiology students of the 2020 intake. Data were collected through questionnaires and analysed using the Chi-Square test. Results: Knowledge with attitudes towards the use of PPE from respondents with good knowledge as much as 21.9% had a positive attitude towards PPE, and 1.0% negative attitude. In addition, respondents with sufficient knowledge 67.6% had a positive attitude, and for 3.8% had a negative attitude. While respondents with less knowledge as much as 6.7% had a positive attitude, and 2.9% had a negative attitude. The results of the correlation coefficient of 0.366 indicated a significant relationship between knowledge and positive attitudes towards the use of PPE. Conclusion: There was a significant relationship between the level of knowledge of nosocomial infections and the attitude of using PPE of anaesthesiology students during clinical practice. Suggestion: There is a need to improve education and training on nosocomial infections and the importance of compliance with the use of PPE for more effective prevention of nosocomial infections. Keyword : Nosocomial Infection Knowledge, Attitude, PPE